'This circle of joy': meaningful musicians' work and the benefits of facilitating singing groups. (19th October 2020) - Forbes, Melissa; Bartlett, Irene
ABSTRACT: The complex realities of musicians' portfolio careers highlight the need for research on musicians' wellbeing. Musicians may include community work within their portfolio such as the facilitation of singing groups for health and wellbeing. Until recently, research on these groups has focused primarily on health and wellbeing outcomes for group participants with little discussion of these factors for the facilitators as professional musicians. We recruited eleven facilitators for semi-structured interviews to investigate their work experiences. Informed by positive psychology and the PERMA model for wellbeing, reflexive thematic analysis of interview data produced themes indicating positive wellbeing outcomes for facilitators. Facilitation was experienced as a unique relationship and mode of performance, and as work ideally suited to facilitators' skills and interests. Facilitators' experiences exhibited all five PERMA elements constitutive of wellbeing: positive emotions (P), engagement (E), relationships (R), meaning (M), and accomplishment (A). These findings align with other research on the positive experiences of professional musicians, music educators and singing group participants, while contributing new understanding that facilitation of these groups can offer wellbeing benefits that compliment musicians' livelihoods. This is important knowledge for the facilitators themselves and for university educators who seek to inform the career choices of their students.